Conditionnements sociaux des vocations sacerdotales en Pologne - Taras, Piotr (Social compass, 1970)
The author draws up certain hypotheses on the social conditioning of priestly and religious vocations in Poland, on the basis of a survey realized in 1962.The survey shows the influence of the family, the social valorisation of the priestly life and the influence of priests, as factors favorable to the nurturing of priestly vocations. On the other hand the pattern of the priestly role, the renouncing of that which is socially valorised are negative factors in certain social environments. A new motivation appears in the social classes where the need for promotion is no longer imperative, linking the religious need to the perfection of the person. Such facts lead to a questionning of the way religion is inserted in society.In a second part, the author tries to understand the reasons for the disproportion noted between the large number of those who desire to enter the seminary and the actual number of candidates. The favorable factors (family environment, in fluence of priests) are neutralised by the attraction of a social success and especially by the image of the Church which perpetuates out-dated patterns of religiosity. The religious appears as peripheral and secondary in society because of the practice of the Church.